PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP KEMAMPUAN REFLEKTIF SISWA SMA - Solahudin, Iman (TarbiyahMU, 2024)
The purpose of this study is to investigate the impact of generative learning models on students' mathematical reflective thinking skills. The generative learning model is an approach that encourages students to explore the knowledge they have to gain new insights. This research was carried out at SMA Negeri 1 Kadipaten for grade XI in the 2023/2024 school year. The approach used was quantitative with a quasi-experimental method, involving 30 students from the experimental class and 30 students from the control class as samples. Sample selection was carried out by purposive sampling technique. Data collection was carried out through reflective thinking ability tests and student response questionnaires. The results showed that hypothesis testing produced a sig. (2-tailed) of 0.000, which indicates the influence of the generative learning model on the reflective ability of high school students.